Strategy for Wasteland Afforestation in Gujarat - Srivastav, Asheem K. (Indian Forester, 1992)
Rapid increase in population on one hand and fast declining woody biomass on the other add to the miseries of mankind. The State of Gujarat is no exception and according to the present estimates it has nearly 8 million hectares of wasted lands. In order to meet the future challenges it is imperative that the productivity of lands must be improved in such a manner that is economically feasible and socially acceptable. Besides sound technical land use planning, other aspects like resource proximity, cost, distribution pattern etc. will have to be taken into consideration in near future. The present paper discusses the strategy that may be adopted for meeting the fuel wood requirement and also the equitable distribution to different sections of the society.